(3EKHGJ WHjYI Gdeecf hCbhi GdMLL Ydi Pdc hGdJfHjg aj aSGOgGs - (3GHf YOj , jMji Hf YOj Hf MejO Hf RcQjG, CHh RcQjG,J (B364 (3g` s
(3ChdgG (B:s
(3hcPG GaVGjdc hMjO TGeGFdc CjgG dGaGVd GdcHjQ GdHG GdChd efgeG ai JMOjO CUfGa CbGhjd GdaGMUjf ZjQ GdeWdhH ajg s
(3BNQgG (B:s
(3abO JHjfJ EPG cejI YOO UaGJ GdHGQF Md GSeg hgPG eG GQOfG Cf fHjf hgPG GceGd ZQVfG afNJJe gPg GdebGdI eY MeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdYTQhfs
(3GfXQg GdeNWhW Qbe (B302 (3ef GdHYKI faSgGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B211s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(4901 / 20) s
Keywords: (3GdadSaI hGdefWbs